Macrozoobenthos community structure in the Western Segara Anakan Lagoon, Central Java, Indonesia - WIYARTI RIMADIYANI; MAJARIANA KRISANTI; SULISTIONO SULISTIONO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rimadiyani W, Krisanti M, Sulistiono. 2019. Macrozoobenthos community structure in the Western Segara Anakan Lagoon, Central Java, Indonesia. Biodiversitas 20: 1588-1596. Anthropogenic activity along the river and around the coastal area will potentially generate waste as it can cause the decline of water quality and affect the lives of macrozoobenthos. This study aimed to study macrozoobenthos community structure in western Segara Anakan Lagoon and its relationship with water physical-chemical quality. The study was conducted from June to November 2016, at six stations of the lagoon. Macrozoobenthos obtained during the study consisted of four phyla (Annelida, Mollusca, Crustacea, and Sipuncula), six classes, and 33 genera. The highest abundance of macrozoobenthos was at Station 6 (193 ind./m2) dominated by Malacostraca and the lowest abundance of macrozoobenthos was at Station 1 (13 ind./m2) dominated by Bivalvia. Diversity, Evenness and dominance indices of the macrozoobenthos were 0.0-2.0, 0-0.8, and 0.4-1.0, respectively, indicating a medium ecologically stressed. Mud substrate condition with high percentage of organic material affected the community structure of the macrozoobenthos expressed by a high density and diversity, but low dominance indices.